(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
This paper extends the information needs and information sources preferred by guardians of children with severe disabilities in managing their children. This research aims to explore the information needs and sources preferred by guardians of children with severe disabilities in Klang valley, Malaysia. The study focused on both personal lives and broader social contexts. Eight common information sources were identified. This paper concentrates on two information sources. Findings showed guardians relied heavily on professional advice. Issues of information needs and information sources preferred by guardians of children with severe disabilities were discussed. Most guardians of children with severe disabilities referred to professionals as their non-printed sources of information, as well as printed sources like newspapers, popular magazines, and pamphlets as their additional information sources. Implications of the findings, study limitations, and recommendation are discussed. A conclusion is that guardians of children with severe disabilities deserve to be provided with a range of ways of meeting their information needs. It is hoped that this study will encourage policy-makers and information service providers to adopt a more holistic approach to meet the needs of families of children with severe disabilities in Malaysian setting.